Multi-physics simulation study of microwave hybrid sintering of aluminium and mechanical characteristics. (October 2022) - Bhoi, Neeraj Kumar; Patel, Deepak Kumar; Singh, Harpreet; Pratap, Saurabh; Jain, Pramod K
In the present study, a finite element model of microwave hybrid sintering along with experimental validation was developed. Multiphysics simulation at 2.45 GHz was carried out to understand the heat transfer behaviour and electric field distribution during the microwave hybrid sintering process. The proposed work presents an innovative and integrated approach for sintering aluminium utilizing microwave energy. Comparison with numerical simulation results and experimental data of temperature variation during microwave hybrid sintering was done. The maximum error predicted by the simulation model and experimental investigation for temperature variation in sintering was found to be within 10%. The X-ray diffraction analysis, relative density and microstructure analysis of the sintered aluminium was done to gain an insight into the material characteristics. The microhardness and nanoindentation tests were carried out to determine the hardness and elastic modulus. Good consolidation behaviour of aluminium with an achieved density of 0.9774, microhardness of 36Hv, nano-hardness as 0.5664 GPa and 57.301 GPa elastic modulus value has been observed. The study will develop a cogent link between the numerical model and experimental data for microwave hybrid sintering.